The Production of Sustainable Low Density Composite Insulation Boards with Vegetable Fibre from Forestry and Agricultural Wastes - Yaşar, Mehmet; Altunok, Mustafa (Fırat University, 2023)
In order to improve the resource generation level of forest and agricultural wastes, it was aimed to use fibrous organic isolation components by choosing pinecones whose seeds have been removed to be used in planting saplings and sunflower stems which need to be removed from the field in order to plant the next crop of sunflower after completing harvesting process. A lot of research is carried out to take advantage of the raw material potential of composite panel products. This study aims to produce an environmentally friendly composite low-density insulation board which can be utilized in structural activities by recycling pinecones and sunflower stems with sustainable vegetable fiber from forestry and agricultural wastes. The highest coefficient of thermal conductivity was found as 147,67 W/mK in samples with a thickness of 40 mm in pinecones with added sunflower stems; the thermal conductivity coefficient was determined as 2,94 W/m2K in samples with a thickness of 50 mm in pinecone. The highest adhesive strength was determined as 162,21 N/mm2 in samples with a thickness of 40 mm in the pinecone with added sunflower stems. The modulus of elasticity was found as 292,05 MPa in samples with a thickness of 40 mm in the pinecone with added sunflower; vertical adhesive strength of the pinecone was determined as 81.89 N/mm2 in samples with a thickness of 50 mm; screw withdrawal resistance was determined as 68,89 N/mm2 in samples with a thickness of 50 mm in pinecones with added sunflower stems.

Orman ve tarım atıklarının kaynak oluşturma seviyesini iyileştirmek amacıyla fidan dikiminde kullanılmak üzere tohumları alınmış çam kozalakları ile hasat süreci tamamlanmış ayçiçeğinin sonraki ürün ekilebilmesi için tarladan uzaklaştırılması gereken ayçiçeği saplarının tercihiyle lifli organik izolasyon bileşenleri kullanılması amaçlanmıştır. Kompozit panel ürünlerinin hammaddesi olma potansiyeli fikrinden yararlanmak için birçok araştırmalar yapılmaktadır. Bu makalede, orman ve tarım atıklarından olan çam kozalağı ile ayçiçeği sapı, sürdürülebilir bitkisel lifli geri dönüştürerek yapısal faaliyetlerde uygulanabilir çevre dostu kompozit düşük yoğunluklu izolasyon levhası üretimi amaçlanmıştır. En yüksek, ısı iletkenlik katsayısı çam kozalağına %6 ayçiçeği sapı katkılı 40 mm kalınlığındaki örneklerde 147,67 W/mK; ısı geçirgenlik katsayısı çam kozalağı 50 mm kalınlığındaki örneklerde 2,94 W/m2K tespit edilmiştir. En yüksek eğilme direnci çam kozalağına %6 ayçiçeği sapı katkılı 40 mm kalınlığındaki örneklerde 162,21 N/mm2; elastikiyet modülü çam kozalağına %6 ayçiçeği sapı katkılı 40 mm kalınlığındaki örneklerde 292,05 MPa; yüzeye dik çekme direnci çam kozalağı 50 mm kalınlığındaki örneklerde 81,89 N/mm2; vida tutma direnci çam kozalağına %6 ayçiçeği sapı katkılı 50 mm kalınlığındaki örneklerde 68,89 N/mm2 tespit edilmiştir.
Orman ve Tarım Atıklarından Sürdürülebilir Bitkisel Lifli Düşük Yoğunluklu Kompozit İzolasyon Levhası Üretimi
Keywords: Wood Based Composites; Ahşap Esaslı Kompozitler; Wooden Buildings and Constructions; Ahşap Yapılar ve Konstrüksiyonları